The influence of the heliogeophysical factors on the clotting of blood of pregnant women with placental insufficiency - E. V. Osipova (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
Geomagnetic storms are one of the natural abiotic risk factors for human health. The response of the organism to their impact depends on the individual adaptive abilities, which were formed during the evolution, but can change in the conditions of pathological processes. Evaluation of the effect of a weak magnetic storm (G4v (22 < Ar < 39 nTl) on hemorheological parameters of blood of pregnant women with placental insufficiency compared to healthy pregnant women showed an increase in platelet count (p = 0.05), fibrinogen content (p = 0.02), thrombocyte (p = 0.03), erythrocyte sedimentation rate (p = 0.004). At the same time, a decrease in the number of red blood cells (p = 0.04), hemoglobin concentration (p = 0.001), hematocrit value (p = 0.0009) was registered. We found a strong direct correlation between subpopulations of platelets, which are characterized by different functional activity. Heterogeneity of platelets, their multidirectional correlations with indicators of blood coagulation system of healthy pregnant women can be considered as a response to the change in the disturbance of the earth's magnetic field. For pregnant women with placental disorders, the magnetic storm was associated with increased activity of the blood coagulation system and a significant increase in its components in the blood of patients. Despite the fact that changes in the blood coagulation system occur from the beginning of pregnancy and are often adaptive, in pregnant women with placental disorders, the additional impact of a weak magnetic storm can be a risk of hemostasis disorders and the development of platelet thrombosis, timely diagnosis and therapy of which is important.